Autologous fat transfer after breast cancer surgery: An exact-matching study on the long-term oncological safety. Issue 10 (October 2019) - Sorrentino, Luca; Regolo, Lea; Scoccia, Elisabetta; Petrolo, Gianfranco; Bossi, Daniela; Albasini, Sara; Caruso, Annalisa; Vanna, Renzo; Morasso, Carlo; Mazzucchelli, Serena; Truffi, Marta; Corsi, Fabio
Abstract: Introduction: Autologous fat transfer (AFT) is widely adopted for breast reconstruction, but its long-term oncologic safety is still not clearly established. The aim of the present study was to compare the 10-year loco-regional recurrence (LRR)-free and distant metastases (DM)-free survival probabilities in AFT vs. control patients, also evaluating the impact of AFT in different intrinsic molecular subtypes of breast cancer. Materials and methods: 464 AFT patients were exactly matched with a cohort of 3100 control patients treated between 2007 and 2017. A multivariate survival analysis was performed accounting for all variables related to LRR and DM, including adjuvant/neoadjuvant treatments. End-points were analyzed both overall and in each molecular subtype. Results: LRR occurred in 6.4% of AFT and in 5.0% of control patients (p = 0.42), while DM were observed respectively in 7.7% and 5.4% of cases (p = 0.20). AFT showed no effect on the 10-year LRR-free survival probability (adjusted HR 0.87, 95%CI 0.43–1.76, p = 0.69) or the 10-year DM-free survival probability (adjusted HR 0.82, 95%CI 0.43–1.57, p = 0.55). Luminal A patients treated by AFT showed a decreased LRR-free survival probability (HR 2.38, 95%CI 0.91–6.17, Log-Rank p = 0.07), which was significantly lower than controls after 80 months (Log-Rank p = 0.02). No differences in the 10-year event-free survival probability were found in Luminal B, HER2-positive or triple-negative patients. Conclusion: AFT does not increase breast cancer recurrence, with the possible exception of late LRRs for Luminal A patients, but further clinical and preclinical data are required to better clarify this data. The use of AFT should not be discouraged.